Lipemic sample: Is it worth our attention? - Nichat, Prachi Bhaurao; Khare, Akhilendra Bahadur; Yadav, Narender Kumar (Indian Journal of Case Reports, 2018)
A 27-year-old male presented to the emergency room with abdominal pain and vomiting. While investigating, the blood sample collected was densely lipemic and repeatedly rejected by the analyzer. On deliberation, the sample was subjected to dilution and results showed hyperglycemia, hypertriglyceridemia (HTG) (>4000 mg/dL), and hyperamylasemia. Acute pancreatitis (AP) was confirmed on computed tomography scan of the abdomen. Lipemic sample while investigating abdominal pain in either pregnant women or patients with diabetes mellitus, hormone disorders, or chronic alcoholism, must prompt the diagnosis of AP (HTG induced pancreatitis). The laboratory should be aware of sample artifacts and efforts should be taken to convey the findings (both physical and biochemical) to the clinician. This case stresses the need for good communication between treating clinical and diagnostic faculties.